A Catholic looks at Spain (circular) - Middleton, J. S.
018a-0021-001 Telegraphic Address: "LABREPCOM, SOWEST, LONDON." Telephone: VICTORIA 8016, 8017, 8018, 8019 THE LABOUR PARTY TRANSPORT HOUSE (South Block), SMITH SQUARE, LONDON. S.W.1 Secretary: J.S. MIDDLETON To Secretaries of Constituency Parties, Literature, & Trade Unions (with copy): Secretaries of Local Labour Parties, Womens Sections and Leagues of Youth. 3rd February, 1937. Dear Secretary, A CATHOLIC LOOKS AT SPAIN Senor Guerra, a distinguished lecturer and writer, a member of the Conservative Party in Spain, has written a moving document which is in the nature of a personal confession of faith. He knows every section of his countrymen intimately. He examines the attitude of the different classes in Spain, and of the Catholic Church of which he is a loyal member. [W]here he criticises the Church is not for its doctrines, its ideals or its ethical and moral standards, it is for the abuses that have crept in. He sees the princes of his Church surrounded by "pampering deference" utterly remote from the interests of the people; the priests, whose doctrine should be one of peace and love, "accomplices and instigators in this monstrous crime, this fratricidal war". He finds that the bourgeoisie feel for the workers a reaI moral aversion, an irresistible scorn". Then he comes to the people and here is his conclusion: "I have chosen the people, humiliated, forgotten, brutalised, and unknown. But I have chosen them also because after long contacts with all classes of society and politics, I have reached the conclusion that it is almost exclusively the people from whom the powerful source of any life now surviving in our country can spring. The Spanish people is the only soul living among the corpses of the 'aristocrats', the fops, the intellectuals (ah! the shameful treachery of the intellectuals), the rich, the politicians, the social climbers, the parvenus, the 'right thinkers', the upper classes." We have published this pamphlet in the hope that it will throw some light on the question of the attitude of Catholics to the troubles in Spain. We hope that it will have a very wide sale, not only for its content but also for the beauty and loftiness of its style and spirit. It is published at 2d. Copies can be obtained post free at 2½d. 1 copy, 1s.6d. 12 copies, 10s. 100 copies. An order form is attached. Yours very sincerely J.S. MIDDLETON, Secretary. 292/946/18a/21